THE ROLE OF BUSINESS ANALYTICS IN STRATEGIC DECISION MAKING - 1. MR. V. VIJAY SWAMINATHAN , 2. M/S K. ARUNA , 3. MRS. P. CHITRA , 4. MRS. MANGAIYARKARASI , 5. DR. N DEEPA , 6. MR. R. RAJESH (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Data analytics plays a pivotal role in modern business decision-making by enabling organizations to convert raw data into valuable insights. Through techniques such as data mining, predictive analytics, and machine learning, businesses can identify patterns, forecast trends, and make evidence-based decisions. This research explores the impact of data analytics on enhancing operational efficiency, improving customer engagement, and gaining competitive advantages. The study also highlights the importance of data-driven strategies in reducing risks and optimizing resources .Ultimately ,it under score show data analytics empowers businesses to make informed decisions in an increasingly data-centric environment.